PENGARUH MANAJEMEN PROGRAM TAHFIDZ TERHADAP BUDAYA RELIGIUS MADRASAH DI MADRASAH IBTIDAIYAH PUI CIRANCA KEC. MALAUSMA - Fani Raihan Fadilah; Moh.Ali; Dewi Cahyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Through the tahfidz program, it is hoped that it will be an appropriate and even effective way to strengthen religious culture for both students and the madrasah environment. Because with the program memorizing the Koran (Hafidz), it is hoped that high religious values will emerge in every student activity by practicing what they have memorized.. The object of Malausma is the influence of the tahfidz program management on the religious culture of the madrasah. Collecting data with technical questionnaires and documentation. The results of this study indicate the effect of the tahfidz al-Qur'an management program on the religious culture of students at Madrasah Ibtidaiyah (MI) PUI Ciranca obtaining a value of 0.016 <0.05, which means that there is a correlation between the management of the tahfidz al-Qur'an program and the formation of religious culture or relationship. Then the correlation coefficient obtained is 0.424 which means that the X variable with the Y variable has a correlation with the degree of relationship at the level of strength which is "Enough" because it is in the 0.40 to 0.60 category with a positive reversed form. It is said to be positive because if the tahfidz program Al-Qur'an is well managed, then a religious culture will be formed within students. Then the correlation correlation (R Square) as in the table. 4.17 shows a number of 0.179 which means that the effect of variable X (management of the tahfidz al-Qur'an program) on variable Y (religious culture) is 17.9% while 82.1% is influenced by other variables.